1974
DOI: 10.1007/bf01221980
|View full text |Cite
|
Sign up to set email alerts
|

Studies in the diabetic Chinese hamster: Light microscopy and autoradiography of pancreatic islets

Abstract: Summary. Light microscopic and autoradiographie studies were performed in normal genetic nondiabetie and diabetic Chinese hamsters after the administration of thymidine-aH and correlated with levels of blood glucose (BG) and plasma insulin (IRI). Pancreatic islets of normal hamsters contained well granulated beta cells; rare islet ceils incorporated thymidine-3H and the IRI/BG ratio (I/G) was = 1.91. l~ecent onset diabetics revealed hyperglycemia and hyperinsulinemia (I/G = 1.97), beta cell degranulation and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…The majority of the intact beta cells represents the group of the functionally active beta cells that have lost GLUT2 immunoreactivity. Confirming previous studies [9,18,19], these intact beta cells showed a well-developed Golgi complex and a large amount of rough endoplasmic reticulum with a marked reduction of secretory granules at the light-and electron-microscopical levels, as well as morphological signs of high insulin biosynthesis and secretory activity. Thus, expression of GLUT2 alone is not a sufficient indicator of glucose responsiveness, as was previously considered in animal models for diabetes [32].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The majority of the intact beta cells represents the group of the functionally active beta cells that have lost GLUT2 immunoreactivity. Confirming previous studies [9,18,19], these intact beta cells showed a well-developed Golgi complex and a large amount of rough endoplasmic reticulum with a marked reduction of secretory granules at the light-and electron-microscopical levels, as well as morphological signs of high insulin biosynthesis and secretory activity. Thus, expression of GLUT2 alone is not a sufficient indicator of glucose responsiveness, as was previously considered in animal models for diabetes [32].…”
Section: Discussionsupporting
confidence: 86%
“…The islet periphery, which is called its mantle, was mainly composed of glucagon (alpha) and somatostatin (delta) cells, whereas the beta cells were mostly localized in the centre of the islet. This confirms earlier observations in this species [9,18,19]. In parallel with the development of diabetes in Chinese hamsters, the morphology of the islet changed.…”
Section: Histology Of the Islets Of Langerhanssupporting
confidence: 89%
See 1 more Smart Citation
“…Pancreatic islet hypertrophy and hyperplasia reported in spontaneous diabetes of other animal species 96 are not found in the diabetic Chinese hamster. However, hypertrophy of the pancreatic beta-cell, 86 increased size of beta-cells, 42 and neoformation of islets from duct cells 16 have been reported in diabetic Chinese hamsters. Replication as measured by 3 Hthymidine incorporation of preexisting beta-cells in diabetic Chinese hamsters has been reported 87 ' 97 though no proof of cell division has been presented in the published literature.…”
Section: Morphologic Changes and Complicationsmentioning
confidence: 99%
“…Like et al [18] have previously published semiquantitative data from autoradiography of pancreatic islets after 'H-thymidine labeling of 3 normal and 9 mild-to-severely diabetic hamsters at different stages of the syndrome. Due to the low number of animals studied and the semiquantitalive technique used for determinations of the labeling frequency, it is difficult to draw firm conclusions from their results.…”
Section: Discussionmentioning
confidence: 99%